Antecedents customer decision to visit Yogyakarta as special regions in Indonesia - Andriani Kusumawati; Karisma Sri Rahayu; Endhar Wijaya Putra (Cogent Business & Management, 2022)
This study aims to clarify the strategies implemented by the government in managing city branding and city image on behavioral interest and to prove the impact of intention to visit on the decision to visit. This research is explanatory research using a quantitative approach, namely conducting a survey directly to respondents using a questionnaire. The population of this study was all domestic tourists in Yogyakarta, a special area in Indonesia who were visiting and obtained a total sample of 280 respondents. Data analysis was carried out using SEM-PLS and processed through the SmartPLS application. The results show that city image has the most dominant influence on intention to visit and then to visit. Therefore, city branding must be appropriately implemented to increase intention and visit to form a positive city image. Intention to visit has proven to mediate city branding and city image on the decision to visit. The study results clarify that the decision to visit can be formed based on the intention to visit, which comes from the stimulus about city branding and city image. This research contributes to the government formulating a strategy for implementing city branding and city image to make the appearance and brand more attractive to create interest in visiting.
Keywords: 650; City branding; city image; decision to visit; intention to visit; tourism policy